1998
DOI: 10.1128/jvi.72.4.3436-3441.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl-Terminal Region of the Human Papillomavirus Type 16 E1 Protein Determines E2 Protein Specificity during DNA Replication

Abstract: The mechanism of DNA replication is conserved among papillomaviruses. The virus-encoded E1 and E2 proteins collaborate to target the origin and recruit host DNA replication proteins. Expression vectors of E1 and E2 proteins support homologous and heterologous papillomaviral origin replication in transiently transfected cells. Viral proteins from different genotypes can also collaborate, albeit with different efficiencies, indicating a certain degree of specificity in E1-E2 interactions. We report that, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…For HPV, the E2 protein is the primary ori recognition protein, as the E2BS is essential but the E1BS is not (8,29,34,35,65). Furthermore, certain combinations of E1 and E2 proteins encoded by heterologous virus types support ori replication with a reduced efficiency or not at all (4,9,79). A direct interaction between pairs of E1 and E2 proteins of the same HPV types or BPV type 1 (BPV-1) has indeed been demonstrated (20,24,43,44,52).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For HPV, the E2 protein is the primary ori recognition protein, as the E2BS is essential but the E1BS is not (8,29,34,35,65). Furthermore, certain combinations of E1 and E2 proteins encoded by heterologous virus types support ori replication with a reduced efficiency or not at all (4,9,79). A direct interaction between pairs of E1 and E2 proteins of the same HPV types or BPV type 1 (BPV-1) has indeed been demonstrated (20,24,43,44,52).…”
mentioning
confidence: 99%
“…However, the specificity and efficiency of replication are significantly enhanced by collaboration with the E2 protein (29,76). In contrast, in transfected cells, both E1 and E2 are required for ori replication, with few exceptions (4,9,54,79). The reasons for the difference in the requirements for E2 between the two replication systems are not completely understood.…”
mentioning
confidence: 99%
“…These findings also indicate that we must exert caution in interpreting the effect of substitutions in the P loop of E1, and perhaps also in that of other NTP-binding proteins, and not assume that these substitutions only affect NTP binding and hydrolysis. Finally, the notion that the precise geometry of the E1 ATP-binding domain is critical for function is also supported by the recent finding that chimeric E1 proteins, in which the junction between HPV-11 and HPV-16 sequences was within the ATPase domain, were unable to support HPV DNA replication (66).…”
Section: Figmentioning
confidence: 87%
“…For BPV-1, an E2binding region was identified between amino acids 200 and 605 of E1, but a slightly larger domain (165 to 605) was required for cooperative binding with E2 at the origin (45). Point mutations and deletions in the BPV-1 E1 C-terminal domain (31), as well as the study of HPV-11-HPV-16 chimeric E1 proteins (66), also indicated a requirement for this region in interaction with E2.…”
mentioning
confidence: 97%
“…HPV DNA replication initiates with the cooperative join of E1 and E2 with specific DNA sequences inside the viral origin [15][16][17]. Formation of this ternary compound E1-E2-ori depends on the interaction between both proteins with DNA, but also there is a critical interaction between the E2 transactivation domain of N-terminal (TAD) and the E1 enzymatic domain of E1 C-terminal [25]. Assembly of this initial complex E1-E2-ori is the starting point for additional E1 molecule recruitment [26,27] and its assembly in hexamers and double hexamers that display activity in ATPase and helicase [28,29].…”
Section: Hpv Life Cyclementioning
confidence: 99%